2020
DOI: 10.1016/j.celrep.2020.107942
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Non-coding RNAs Promotes Recycling of Termination Factors at Sites of Transcription

Abstract: Highlights d Degradation of ncRNAs by the exosome frees bound termination factors Nab3 and Nrd1 d Exosome inhibition triggers accumulation of ncRNAs complexed with Nab3 and Nrd1 d Out-titration of Nab3 and Nrd1 by ncRNAs decreases NNS co-transcriptional binding d A circular RNA decoy recapitulates the global impairment of NNS-dependent termination

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
(95 reference statements)
2
20
0
Order By: Relevance
“…We have recently shown that inhibition of the exosome in yeast cells leads to the accumulation of ncRNAs complexed with Nab3 and Nrd1, decreasing recycling of these termination factors to sites of transcription and inducing global termination defects at NNS targets. Consistent with the notion that ncRNAs out-titrate Nab3 and Nrd1 termination factors, we have shown that a similar genomewide termination impairment could be achieved by expressing a circular RNA decoy containing a Nab3 binding target [1] . In relation to this previous research article, here we expand our observations on the effect of the circular RNA decoy on NNS termination.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…We have recently shown that inhibition of the exosome in yeast cells leads to the accumulation of ncRNAs complexed with Nab3 and Nrd1, decreasing recycling of these termination factors to sites of transcription and inducing global termination defects at NNS targets. Consistent with the notion that ncRNAs out-titrate Nab3 and Nrd1 termination factors, we have shown that a similar genomewide termination impairment could be achieved by expressing a circular RNA decoy containing a Nab3 binding target [1] . In relation to this previous research article, here we expand our observations on the effect of the circular RNA decoy on NNS termination.…”
supporting
confidence: 86%
“…1 Schematic representation of the experimental rationale. As previously shown in the related research paper [1] , out-titration of the Nrd1-Nab3 RNA-binding module by excess ncRNA accumulating in exosome-impaired rrp6∆ cells or by expression of a circular ncRNA decoy leads to a decrease in its free pool (indicated by transparency). The overall CRAC signal is contributed by both co- and post-transcriptionally bound Nrd1-Nab3 to the RNA.…”
Section: Data Descriptionmentioning
confidence: 52%
See 3 more Smart Citations